Pengaruh Struktur Modal, Investment Opportunity Set, Ukuran Perusahaan, Return On Asset dan Likuiditas terhadap Kualitas Laba pada Perusahaan Jasa yang Terdaftar di Bursa Efek Indonesia - Bayu Wulandari; Angela Juliananda Situmorang; Donna Valentina Sinaga; Editha Laia (Owner : Riset dan Jurnal Akuntansi, 2021)
Abstract The purpose of this study was to see and test the effect of Capital Structure, Investment Opportunity Set (IOS), Company Size, Return on Asset (ROA) and Liquidity on Earning Quality at Service Companies listed on the IDX (Indonesia Stock Exchange) in 2017-2019. This research uses the quantitative descriptive approach. The population obtained was 79 companies listed on the IDX (Indonesia Stock Exchange) from 2017-2019. Samples were taken by using purposive sampling technique. This technique is also often used by other researchers because the obtained samples are closer to the research objectives. The obtained samples were 16 companies. The data analysis used various kind of analysys, namely ; the multiple linear analysis, the coefficient of determination test, the classical assumption test, the F test and the t test. This result of this study shows that, partially, the Capital Structure, Investment Opportunity Set (IOS), Company Size, Return on Asset (ROA) and Liquidity did not significantly affect the Earning Quality listed on the IDX (Indonesia Stock Exchange) in 2017-2019. Neither, simultaneously, the Capital Structure, Investment Opportunity Set (IOS), Company Size, Return on Asset (ROA) and Liquidity is significant on the Earning Quality at Service Companies listed on the IDX (Indonesia Stock Exchange) in 2017-2019. Keywords : Capital Structure, Investment Opportunity Set, Company Size, Return on Asset and Liquidity (Current Ratio).